Biodiversity, trait composition and ecological functioning: impacts of coastal urbanisation on subtropical mudflats - Navodha G Dissanayake; Christopher L J Frid; Bryony A Caswell (PANGAEA, 2020)
The World extquotesingles coastlines are being heavily modified at an alarming rate due to urbanisation which threatens natural coastal ecosystem health and biodiversity. The datasets represent the observed abundance of macrofauna (retained on a 0.5mm mesh sieve) retrieved from 24 subtropical mudflats along the south-east coast of Australia in 25cm x 25cm box cores and 50cm x 50cm quadrats (to a sediment depth of 11cm). Sites were located between south Deception Bay and Tallebudgera, Gold Coast. Sampling was carried out in winter 2016 (July-August) and summer 2017 (January-February). The summer assemblages contained more species, more individuals and had differing taxonomic composition. The 24 sites were categorised into four land-use sub-catchments e.g. high industry, low industry, residential and peri-urban (see paper for categories and site classifications). When indexed as a proportion of sub-catchment area, urbanisation did not correspond to a clear impact on macrofaunal composition; rather the nature of industry or activity was critical. Species biological traits were analysed using biological traits analysis which captured their life habit, morphology and behaviour (see accompanying paper for methods). Sediment properties such as the redox discontinuity layer (RDL) depth, organic matter content (as percentage on loss on ignition) and the proportion of silt and clay sized particles (in the top 11cm) and benthic chlorophyll a concentration (top 2 cm of sediment) were measured in triplicate toe describe each site with respect to urban gradients. Finally, the biological traits of mudflat macrofauna assemblages were compared to determine the effects of urbanisation on ecological functioning and delivery of ecosystem services of mudflats. The data revealed that functioning was conserved in mudflats experiencing current levels of enrichment, but this may decline with growing pressure from human populations. The results of this study illustrate that large-scale spatial data, such as from satellites, can be used to detect the cumulative effects of urbanisation when the pressures are highly resolved.